2012
DOI: 10.2147/ijn.s27994
|View full text |Cite
|
Sign up to set email alerts
|

Probable biofilm formation in the cheek as a complication of soft tissue filler resulting from improper endodontic treatment of tooth 16

Abstract: Injectable filling agents offer the promise of a better appearance without surgery and, among them, hyaluronic acid is the most commonly used. Although complications are rare, it is necessary to know the possible side effects and complications in order to be prepared for their management. That is why many researchers have been focusing on the interactions between hyaluronic acid and pathogens, inflammatory mediators, the immune system, and markers of oxidative stress to achieve efficient drug delivery, given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…More sophisticated ways to improve performance might include novel antimicrobials to help penetrate or dissolve biofilm. Recent studies have shown that infection is more likely when a bolus of biofilm is injected than individual planktonic cells345459. Filler materials that resist colonization or contain anti-biofilm components may also interfere with colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated ways to improve performance might include novel antimicrobials to help penetrate or dissolve biofilm. Recent studies have shown that infection is more likely when a bolus of biofilm is injected than individual planktonic cells345459. Filler materials that resist colonization or contain anti-biofilm components may also interfere with colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Wounds or dermatitis may also harbor increased bioburden. Another source of contamination is injection through colonized oral or nasal mucosa, which is more likely to have mature biofilm34.…”
mentioning
confidence: 99%
“…Addressing the above mentioned complications is crucial due to the increase in the clinical use of hyaluronic acid, not only in the aesthetic medicine clinic,17,18,19 but also in restorative medicine20 and for the treatment of other pathologies, such as lower-leg telangiectasia,21 premature ejaculation,22 and osteoarthritis 23,24,25…”
Section: Aimmentioning
confidence: 99%
“…Further studies have also shown that HA possesses antibacterial, antifungal [ 17 ], and antiviral activities [ 18 ]. Due to its biological properties, HA has been extensively used in experimental and clinical osteoarthritis [ 19 21 ], lower-leg telangiectasia [ 22 ], premature ejaculation [ 23 ], and restorative and esthetic surgery [ 24 26 ]. However, to date, no clinical study has shown an effectiveness of a compound based on HA and CS on gastritis-related upper abdominal pain/discomfort and endoscopic features.…”
Section: Introductionmentioning
confidence: 99%